The Routledge companion to global economics (Routledge, 2017)
Combining the in-depth background coverage of an encyclopedia, with the quick look-up convenience of a dictionary, this new work is an invaluable resource for anyone concerned with international economics. The only reference work to cover the latest theories in the vital field of global economics, The Routledge Companion to Global Economics explores new economic thought from A-Z, and offers full-length survey discussions by the most respected experts in the field.